2012
DOI: 10.1080/03004430.2011.630733
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing relates to attachment to childhood comfort objects of college students

Abstract: The author tested the hypothesis that attachment to comfort objects is based on the sensory processing characteristics of the individual. Fifty-two undergraduate students with and without a childhood comfort object reported sensory responses and performed a tactile threshold task. Those with a comfort object described their object and rated their attachment to it. Participants with a strong attachment liked the texture of their comfort object and sleeping with it. Smell sensitivity in childhood, seeking out ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Most particularly, a normative model of what types of objects should provide comfort to neurotypical children and adults may not be most appropriate for individuals with autism. Understanding that sensory processing may be different in children with autism (Marco, Hinkley, Hill, & Nagarajan, 2011) and that this impacts upon relationships with objects of attachment and security (Kalpidou, 2012) is relevant to practice.…”
Section: Discussionmentioning
confidence: 99%
“…Most particularly, a normative model of what types of objects should provide comfort to neurotypical children and adults may not be most appropriate for individuals with autism. Understanding that sensory processing may be different in children with autism (Marco, Hinkley, Hill, & Nagarajan, 2011) and that this impacts upon relationships with objects of attachment and security (Kalpidou, 2012) is relevant to practice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as the impromptu memorials that appear after a school shooting testify, comfort or tactile objects-such as stuffed animals and dolls-have been found to support recovery from tragedies and trauma (Kalpidou, 2012). However, the implementation of comfort and/or tactile objects to support college students after a tragedy or trauma has not been well researched, with Kalpidou's (2012) study on the effect of childhood comfort objects relating to college students' sensory processing being an outlier in the field of higher education. In addition, no studies have explored how a comfort/tactile object could improve student-to-Title IX office communication of sexual violence or any other incident under Title IX's purview (such as gender discrimination in the workplace).…”
Section: Conceptualizing Leto the Lion A Ccomentioning
confidence: 96%
“…Given that many species have no such mechanism, it is a question of interest as to how and when objects became important in this way. Kalpidou (2012) found that attachment to a comfort toy or object is related to tactile processing, with those who have a higher tactile threshold and who seek out more tactile stimulation being more likely to have such an object. This could suggest a biological mechanism that contributed to evolution selection for this mechanism.…”
Section: Introductionmentioning
confidence: 99%